Severe Liver Injury while Using Umbilical Venous Catheter: Case Series and Literature Review - Grizelj, Ruza; Vukovic, Jurica; Bojanic, Katarina; Loncarevic, Damir; Stern-Padovan, Ranka; Filipovic-Grcic, Boris; Weingarten, Toby N.; Sprung, Juraj (American Journal of Perinatology, 2014)
Objective Proper position of umbilical venous catheter (UVC) is of importance to avoid severe complications. We review clinical presentations of neonates with UVC who developed catheter-associated liver injury.Study Design We reviewed institutional intensive care database (2008–2013) and identified neonates with UVCs who developed severe hepatic injury. We recorded admission diagnosis, gestational age, birth weight, number of days the umbilical catheter was in place, its radiological position at insertion and at the time of injury, presenting clinical signs, and outcomes.Results Of 1,081 neonates, 9 (0.8% [95% exact binomial confidence interval, 0.4–1.6%]) with UVC developed severe hepatic injury. All had the UVC malpositioned within the liver circulation. All presentations were life threatening, with acute abdominal distension (hepatomegaly) being the most consistent sign. Two neonates died from complications which were unrelated to catheter-associated liver injury.Conclusions: In all neonates with liver injury, UVC was malpositioned within the portal circulation. Despite the fact that our report provides only circumstantial evidence for the mechanism of injury, it supports reports which suggest that “low” UVC position increases potential for this type of complication. Acute onset of abdominal distension in a neonate with UVC should prompt ultrasonographic evaluation of position of the catheter tip.
Keywords: catheter malposition; complications; liver injury; thoracoabdominal radiographs; ultrasonography; umbilical venous catheter